GalileoMobile: inspiring young people under the same sky - Torres Machado, Diego (Cadernos de Astronomia, 2022)
GalileoMobile is a non-profit, itinerant, science education initiative that brings modern Astronomy to young people in developing countries, especially in areas with little access to extension or scientific dissemination programs. In this article, its history is reported, with emphasis on projects carried out in Brazil and also on its most recent project, Amanar.